ISLAM, MINORITAS DAN PLURALISME DI INDONESIA - Moh Hasim (Balai Penelitian dan Pengembangan Agama Semarang, 2008)
Because of governmental system that acknowledged six officialreligions (Islam, Christian, Catholic, Hindu, Buddha, and Confucius),Indonesia as democratic country are judged by international worlddoing religious discrimination on other religious minority group(outside official religion). The role of MUI as authoritative religiousagency, exactly, worsen religious belief conflicts by giving label